Immunological correlates of protection afforded by PHV02 live, attenuated recombinant vesicular stomatitis virus vector vaccine against Nipah virus disease - Monath, Thomas P.; Nichols, Richard; Feldmann, Friederike; Griffin, Amanda; Haddock, Elaine; Callison, Julie; Meade-White, Kimberly; Okumura, Atsushi; Lovaglio, Jamie; Hanley, Patrick W.; Clancy, Chad S.; Shaia, Carl; et al. (Frontiers in Immunology, 2023)
Immune correlates of protection afforded by PHV02, a recombinant vesicular stomatitis (rVSV) vector vaccine against Nipah virus (NiV) disease, were investigated in the African green monkey (AGM) model. Neutralizing antibody to NiV has been advanced proposed as the principal mediator of protection against future NiV infection. Two approaches were used to determine the correlation between neutralizing antibody levels and outcomes following a severe (1000 median lethal doses) intranasal/intratracheal (IN/IT) challenge with NiV (Bangladesh): 1) reduction in vaccine dose given 28 days before challenge and 2) challenge during the early phase of the antibody response to the vaccine. Reduction in vaccine dose to very low levels led to primary vaccine failure rather than a sub-protective level of antibody. All AGMs vaccinated with the nominal clinical dose (2 x 10 7 pfu) 21, 14 or 7 days before challenge survived. AGMs vaccinated 21 days before challenge had neutralizing antibodies [geometric mean titer (GMT) 71.3]. AGMs vaccinated 7 or 14 days before challenge had either undetectable or low neutralizing antibody titers pre-challenge but a rapid rise in titers after challenge that abrogated NiV infection. A simple logistic regression model of the combined studies was used in which the sole explanatory variable was pre-challenge neutralizing antibody titers. For a prechallenge titer of 1:5, the predicted survival probability is 100%. The majority of animals with pre-challenge neutralizing titer of ≥1:20 were protected against pulmonary infiltrates on thoracic radiograms; and a majority of those with titers ≥1:40 were protected against clinical signs of illness and against a ≥fourfold antibody increase following challenge (indicating sterile immunity). Controls receiving rVSV-Ebola vaccine rapidly succumbed to NiV challenge, eliminating innate immunity stimulated by the rVSV vector as a contributor to survival in monkeys challenged as early as 7 days after vaccination. It was concluded that PHV02 vaccine elicited rapid onset of protection and that any detectable level of neutralizing antibody was a functional immune correlate of survival.